2021
DOI: 10.34172/jlms.2021.73
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of a 940 nm Diode Laser With/ Without Silver Nanoparticles Against Enterococcus faecalis

Abstract: Introduction: The final goal of root canal therapy is to remove of the most bacteria from the root canal. This study aimed at comparing the antibacterial effects of a diode laser with a wavelength of 940nm and silver nanoparticles and the synergic effects of both techniques on Enterococcus faecalis. Methods: Ninety single-rooted human teeth were decoronated and prepared with rotary files. The samples were irrigated with sodium hypochlorite and EDTA17%. Then they were autoclaved and contaminated with E. faecali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Hendi. et al (2021, compared the activated silver nanoparticle irrigant by diode laser 940 nm for 15 sec at 3 times interval together with 5% NaOCI on E. faecalis bacteria and found that NaOCI was significantly more effective [42]. They concluded that laser irradiation could not enhance the effect of silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Hendi. et al (2021, compared the activated silver nanoparticle irrigant by diode laser 940 nm for 15 sec at 3 times interval together with 5% NaOCI on E. faecalis bacteria and found that NaOCI was significantly more effective [42]. They concluded that laser irradiation could not enhance the effect of silver nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, irradiation with a diode laser generates thermal and photo-disruptive energy leading to a sublethal damage of the bacteria present in contact with and near the site of irradiation [ 32 ]. The heat and photo-disruptive energy can reach deep areas that the conventional mechanical debridement cannot [ 32 , 33 , 34 ]. For instance, this might have increased the disinfection of the epithelial junction, the connective tissue and the periodontal ligaments [ 19 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The heat and photo-disruptive energy can reach deep areas that the conventional mechanical debridement cannot [ 32 , 33 , 34 ]. For instance, this might have increased the disinfection of the epithelial junction, the connective tissue and the periodontal ligaments [ 19 , 32 , 33 , 34 ]. In addition, the 980 nm wavelength is in the near infrared light that was shown to be able to directly kill pigmented bacteria that contain protoporphyrin IX such as Aggregatibacter actinomycetemcomitans [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…That was followed by diode laser (Epic X ™, BIOLASE Tech, Irvine, USA) for the activation process, diode laser (ʎ = 940 nm, 1W, source power) was utilized using the E2-14 tip, an endo 200 µm flexible laser tip with a 14 mm length, 1 mm short of the working length, in continuous mode, using the same irradiation protocol as previously mentioned [ 27 ].…”
Section: The Inclusion Criteria Were As Followsmentioning
confidence: 99%